2021
DOI: 10.3390/foods10102348
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Fermentation Strategy on the Flavour Formation of Ilzer Rose (Malus domestica Borkh.) Apple Wine

Abstract: The flavour and the volatilome of apple wines made from the Austrian heritage variety Ilzer Rose was in the scope of this study. The apple wines were produced by adopting oenological practises that are not commonly used in fruit wine production. Different fermentation strategies including the addition of enzymes with β-glucosidase activity, addition of a fining agent, maceration of the mash along with mash fermentation were applied. The volatile compounds of the juices as intermediates and the resulting apple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…CATA allowed us to quickly assess a broad range of sensory attributes. While this technique is primarily used with consumers, examples from oenology and also from our own previous research have proved to give good results when CATA is combined with a lower number of trained panelists [ 24 , 25 , 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…CATA allowed us to quickly assess a broad range of sensory attributes. While this technique is primarily used with consumers, examples from oenology and also from our own previous research have proved to give good results when CATA is combined with a lower number of trained panelists [ 24 , 25 , 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…Some of the esters in the base cider formed during fermentation were broken down during the secondary fermentation stage. Recent investigations have shown that the most common volatile compounds in ciders and sparkling ciders are higher alcohols [50,51]. The amount of higher alcohols produced during fermentation through the Ehrlich pathway is significantly influenced by amino acids, which are a source of nitrogen for yeasts [52].…”
Section: Volatile Compounds In Sparkling Cidermentioning
confidence: 99%
“…Apple wines and ciders obtained through apple fermentation are particularly popular in Europe, North America, and Australia. The ethanol content of wines and ciders varies, with ciders usually containing less than 8.25% and apple wines containing more than 8.25% [ 82 , 83 , 84 , 85 , 86 ]. The production of apple wines is similar to that of grape wines and involves several stages, including fruit maceration, pressing, must fermentation with malolactic fermentation, ageing and stabilisation, and bottling [ 83 , 87 , 88 , 89 ].…”
Section: Volatile Compounds Of Apple Wines and Cidersmentioning
confidence: 99%
“…Ruppert et al [ 83 ] investigated the impact of the maceration of apple pomace during wine vinification on the profile of volatile compounds. They observed an increase in the concentration of butanoic acids 1-pentanol, 1-hexanol, 1-heptanol, 1-octanol, and benzyl alcohol after maceration, whereas the amount of the hexanoic acid 3-ethoxy-1-propanol decreased.…”
Section: Volatile Compounds Of Apple Wines and Cidersmentioning
confidence: 99%